ISSUES OF LINGUOCULTURAL STABILIZATION OF PROFESSIONAL LEXICON IN DIFFERENT LANGUAGES - Imomov Elyor Abdikarimovich (Galaxy International Interdisciplinary Research Journal, 2022)
The purpose of the article is to illustrate some terms which are utilized in special profession. Moreover, it discusses linguocultural characteristics of the words and similarities as well as differences between some languages.